Iqbal’s and Hassan’s complaints: a study of “To the Holy Prophet” and “SMS to sir Muhammad Iqbal” - Hasan, Md. Mahmudul (Wiley, 2020)
Muhammad Iqbal and Mohd. Kamal Hassan respectively wrote “To the Holy Prophet” and “SMS to Sir Muhammad Iqbal” in the 1930s and in the 2000s – two extremely challenging times, as in the former most Muslim‐majority countries were under European colonial rule and in the latter, Western global powers wove an all‐pervasive web of domination and exploitation of them. They focus on the internal weaknesses of subjugated Muslims and lament that, since the attitude of many of them is characterized by inaction and reliance on others, domination by foreign powers became an inevitable corollary. A culture of self‐indulgence, stagnation, and complacency precipitated their decline and facilitated their exploitation by powerful outside interests. In their pursuit to understand the reasons for Western domination over Muslim societies, they studied the “moral paralysis” of colonized Muslims in order to reform them. Accordingly, their analysis of the subordinate position of Muslim peoples and countries can clearly be viewed through the lens of Bennabi’s notion of “colonizability,” as Iqbal’s and Hassan’s complaints in the poems mostly involve exposing several of their weaknesses that prevented them from playing their actual role, and hindered them from realising their potential, in the world.